Palaeozoic and Pliocene tectonic evolution of the Salt Range constrained by low‐temperature thermochronology. (24th December 2020) - Ghani, Humaad; Sobel, Edward R.; Zeilinger, Gerold; Glodny, Johannes; Zapata, Sebastian; Irum, Irum
Abstract: The Salt Range in Pakistan exposes Precambrian to Pleistocene strata outcropping along the Salt Range Thrust (SRT). To better understand the in‐situ Cambrian and Pliocene tectonic evolution of the Pakistan Subhimalaya, we have conducted low‐temperature thermochronological analysis using apatite (U‐Th‐Sm)/He and fission track dating. We combine cooling ages from different samples located along the thrust front of the SRT into a thermal model that shows two major cooling events associated with rifting and regional erosion in the Late Palaeozoic and SRT activity since the Pliocene. Our results suggest that the SRT maintained a long‐term average shortening rate of 5–6 mm/yr and a high exhumation rate above the SRT ramp since 4 Ma.